Pengaruh Model Pembelajaran PMRI terhadap Pemahaman Konsep Matematika - Retno Nengsih (Universitas Indraprasta PGRI Jakarta, 2018)
Understanding or comprehension is the ability of a person to fully understand something based on the situation, concept, and facts he has. Understanding is knowledge achieved through the process of understanding something. The level of understanding depends on the appropriate existing ideas and the establishment of new relationships between ideas. In mathematics, increasing understanding of concepts can be done using the PMRI learning model. Therefore, teachers must find a realistic problem related to learning materials and students’ daily life. This research aims to find out the effect of a learning model on the understanding of mathematical concepts. The research is an experimental study with samples of 60 testees. The hypothesis testing technique used is a one-way t test which consists of one independent variable, which is the learning model, and one dependent variable, which is the understanding of mathematical concepts. This research is carried out in Central Jakarta Public Senior High School, DKI Jakarta in 2015. From the research results, it can be concluded that there is an insignificant effect of a learning model on the understanding of mathematical concepts